anonymous
  • anonymous
Solve the equation: −4(x + 10) − 6 = −3(x − 2
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Solve for x: -6-4 (x+10) = -3 (x-20) Distribute -4 over x+10. -4 (x+10) = -40-4 x: -40-4 x-6 = -3 (x-20) Group like terms in -4 x-40-6. Grouping like terms, -4 x-40-6 = -4 x+(-6-40): -4 x+(-6-40) = -3 (x-20) Evaluate -6-40. -6-40 = -46: -46-4 x = -3 (x-20) Factor the polynomial, -4 x-46. Factor -2 from the polynomial -46-4 x: -2 (2 x+23) = -3 (x-20) Move everything to the left hand side. Add 3 (x-20) to both sides of -2 (2 x+23) = -3 (x-20): 3 (x-20)-2 (2 x+23) = 3 (x-20)-3 (x-20) Look for two terms that sum to zero. 3 (x-20)-3 (x-20) = 0: 3 (x-20)-2 (2 x+23) = 0 Distribute -2 over 2 x+23. -2 (2 x+23) = -46-4 x: -46-4 x+3 (x-20) = 0 Distribute 3 over x-20. 3 (x-20) = 3 x-60: 3 x-60-4 x-46 = 0 Group like terms in 3 x-4 x-60-46. Grouping like terms, 3 x-4 x-60-46 = (3 x-4 x)+(-46-60): (3 x-4 x)+(-46-60) = 0 Combine like terms in 3 x-4 x. 3 x-4 x = -x: -x+(-46-60) = 0 Evaluate -46-60. -46-60 = -106: -106-x = 0 Isolate terms with x to the left hand side. Add 106 to both sides: (106-106)-x = 106 Look for two terms that sum to zero. 106-106 = 0: -x = 106 Solve for x. Multiply both sides of -x = 106 by -1: -x/(-1) = -106 Any nonzero number divided by itself is one. (-1)/(-1) = 1: Answer: | | x = -106 If you liked my repsonse, please give me the best response!
jonathanvaldes98
  • jonathanvaldes98
Simplifying -4(x + 10) + -6 = -3(x + -2) Reorder the terms: -4(10 + x) + -6 = -3(x + -2) (10 * -4 + x * -4) + -6 = -3(x + -2) (-40 + -4x) + -6 = -3(x + -2) Reorder the terms: -40 + -6 + -4x = -3(x + -2) Combine like terms: -40 + -6 = -46 -46 + -4x = -3(x + -2) Reorder the terms: -46 + -4x = -3(-2 + x) -46 + -4x = (-2 * -3 + x * -3) -46 + -4x = (6 + -3x) Solving -46 + -4x = 6 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -46 + -4x + 3x = 6 + -3x + 3x Combine like terms: -4x + 3x = -1x -46 + -1x = 6 + -3x + 3x Combine like terms: -3x + 3x = 0 -46 + -1x = 6 + 0 -46 + -1x = 6 Add '46' to each side of the equation. -46 + 46 + -1x = 6 + 46 Combine like terms: -46 + 46 = 0 0 + -1x = 6 + 46 -1x = 6 + 46 Combine like terms: 6 + 46 = 52 -1x = 52 Divide each side by '-1'. x = -52 Simplifying x = -52

Looking for something else?

Not the answer you are looking for? Search for more explanations.